Two faces of power. Cohesion and diversification in government elites. A study of two executives in Spain - Villena-Oliver, Andrés (My University, 2014)
La comunicación presenta algunos resultados del anàlisis de dos ejecutivos españoles (2004 y 2012)
Keywords: Comunicación - Análisis de red; Political elite; Government; Social network analysis